Cost-Utility Analysis: Sartorius Flap versus Negative Pressure Therapy for Infected Vascular Groin Graft Managment. Issue 11 (November 2015) - Chatterjee, Abhishek; Macarios, David; Griffin, Leah; Kosowski, Tomasz; Pyfer, Bryan J.; Offodile, Anaeze C.; Driscoll, Daniel; Maddali, Sirish; Attwood, John
Abstract : Background: Sartorius flap coverage and adjunctive negative pressure wound therapy (NPWT) have been described in managing infected vascular groin grafts with varying cost and clinical success. We performed a cost–utility analysis comparing sartorius flap with NPWT in managing an infected vascular groin graft. Methods: A literature review compiling outcomes for sartorius flap and NPWT interventions was conducted from peer-reviewed journals in MEDLINE (PubMed) and EMBASE. Utility scores were derived from expert opinion and used to estimate quality-adjusted life years (QALYs). Medicare current procedure terminology and diagnosis-related groups codes were used to assess the costs for successful graft salvage with the associated complications. Incremental cost-effectiveness was assessed at 50, 000/QALY, and both univariate and probabilistic sensitivity analyses were conducted to assess robustness of the conclusions. Results: Thirty-two studies were used pooling 384 patients (234 sartorius flaps and 150 NPWT). NPWT had better clinical outcomes (86.7% success rate, 0.9% minor complication rate, and 13.3% major complication rate) than sartorius flap (81.6% success rate, 8.0% minor complication rate, and 18.4% major complication rate). NPWT was less costly (12, 366 versus 23, 516) and slightly more effective (12.06 QALY versus 12.05 QALY) compared with sartorius flap. Sensitivity analyses confirmed the robustness of the base case findings; NPWT was either cost-effective at 50, 000/QALY or dominated sartorius flap in 81.6% of all probabilistic sensitivity analyses. Conclusion: In our cost–utility analysis, use of adjunctive NPWT, along with debridement and antibiotic treatment, for managing infected vascular groin graft wounds was found to be a more cost-effective option when compared with sartorius flaps.